Step
*
2
of Lemma
ps-sigma-unelim-elim-term
1. C : SmallCategory
2. X : ps_context{j:l}(C)
3. A : {X ⊢ _}
4. B : {X.A ⊢ _}
5. SigmaUnElim o SigmaElim = 1(X.Σ A B) ∈ psc_map{j:l}(C; X.Σ A B; X.Σ A B)
6. T : {X.Σ A B ⊢ _}
7. t : {X.Σ A B ⊢ _:T}
8. SigmaUnElim o SigmaElim
= 1(X.Σ A B)
∈ {z:psc_map{j:l}(C; X.Σ A B; X.Σ A B)| 
   (z = SigmaUnElim o SigmaElim ∈ psc_map{j:l}(C; X.Σ A B; X.Σ A B))
   ∧ (z = 1(X.Σ A B) ∈ psc_map{j:l}(C; X.Σ A B; X.Σ A B))} 
9. (t)SigmaUnElim o SigmaElim = (t)1(X.Σ A B) ∈ {X.Σ A B ⊢ _:T}
⊢ ((t)SigmaUnElim)SigmaElim = t ∈ {X.Σ A B ⊢ _:T}
BY
{ (NthHypEqGen (-1) THEN EqCDA THEN Auto) }
Latex:
Latex:
1.  C  :  SmallCategory
2.  X  :  ps\_context\{j:l\}(C)
3.  A  :  \{X  \mvdash{}  \_\}
4.  B  :  \{X.A  \mvdash{}  \_\}
5.  SigmaUnElim  o  SigmaElim  =  1(X.\mSigma{}  A  B)
6.  T  :  \{X.\mSigma{}  A  B  \mvdash{}  \_\}
7.  t  :  \{X.\mSigma{}  A  B  \mvdash{}  \_:T\}
8.  SigmaUnElim  o  SigmaElim  =  1(X.\mSigma{}  A  B)
9.  (t)SigmaUnElim  o  SigmaElim  =  (t)1(X.\mSigma{}  A  B)
\mvdash{}  ((t)SigmaUnElim)SigmaElim  =  t
By
Latex:
(NthHypEqGen  (-1)  THEN  EqCDA  THEN  Auto)
Home
Index